A multifunctional 3D dressing unit based on the core–shell hydrogel microfiber for diabetic foot wound healing. (7th April 2022) - Huang, Qiwei; Wu, Tingbin; Wang, Lihuan; Zhu, Jichang; Guo, Yongshi; Yu, Xi; Fan, Longfei; Xin, John H.; Yu, Hui
Abstract : Multifunctional (moisture absorption and retention, antibacterial activity, biocompatibility, and adjustable drug release) diabetic wound dressing in coaxial 3D bioprinting. Abstract : The healing mechanism of diabetic foot wounds is very complicated, and it is difficult for a single-function medical dressing to achieve good therapeutic effects. We propose a simple coaxial biological 3D printing technology, which uses one-step 3D deposition to continuously produce multifunctional medical dressings on the basis of core–shell hydrogel fibers. These dressings have good biocompatibility, controlled drug-release performance, excellent water absorption and retention, and antibacterial and anti-inflammatory functions. In vivo experiments with type 2 diabetic rats were performed over a 14-day period to compare the performance of the multifunctional 3D dressing with a gauze control; the multifunctional 3D dressing reduced inflammation, effectively increased the post-healing thickness of granulation tissue, and promoted the formation of blood vessels, hair follicles, and highly oriented collagen fiber networks. Therefore, the proposed multifunctional dressing is expected to be suitable for clinical applications for healing diabetic foot wounds.